A conceptual framework for understanding the mechanism of action of community health workers services: the centrality of social support. (8th December 2017) - Taylor, Beck; Mathers, Jonathan; Parry, Jayne
Abstract: Objective: To propose an empirically derived and theoretically-informed mechanism to explain how Community Health Workers (CHWs) bring about health gain in clients in England. Methods: We undertook in-depth interviews ( n = 43) with CHWs and service staff working in four case studies selected using maximum variation sampling. Interviewees were encouraged to talk about the service, how they had become involved with the service, the CHW role and relationship with clients. Findings: We identified the provision of social support to be central to the mechanism of CHW-mediated health gain. Appropriate social support provision comprised three inter-related elements; needs assessment, social support delivery and client engagement. This mechanism is dependent on the personal characteristics of CHWs and of the roles they are employed or volunteer to carry out. Conclusion: A range of CHW characteristics can influence the social support process, but these are context-dependent and move beyond simple notions of CHW similarity to the client. This finding has important policy implications for the development and implementation of CHW services in high income countries with super-diverse populations.